3(x-3)=12+x

Simple and best practice solution for 3(x-3)=12+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)=12+x equation:


3(x-3)=12+x

We simplify the equation to the form, which is simple to understand
3(x-3)=12+x

Reorder the terms in parentheses
+(+3x-9)=12+x

Remove unnecessary parentheses
+3x-9=+12+x

We move all terms containing x to the left and all other terms to the right.
+3x-1x=+12+9

We simplify left and right side of the equation.
+2x=+21

We divide both sides of the equation by 2 to get x.
x=10.5

See similar equations:

| -3x+8=1-4x | | 6x+3=2x-21 | | 10x^2-18x+12=0 | | 4+7=-9 | | 4x-6=12x-30 | | 3x+2y=-14 | | (-5+x)/2=3 | | -2(x)-(3)=12+(x) | | 5(x+3)+6x=136 | | -2x-(3)=12+(x) | | 4m+12=112 | | 20a+14b+2c+5c-4b-2a= | | 0.12x+0.02x=50000 | | 7+7(x)=8+6(x) | | a+5*2=9 | | 3m+12=112 | | 11x=6x-15 | | 4x^2-2x=6x^2-2(x^2-x) | | x^4+7x^3+11x^2-7x-12=0 | | 9x+2x-4x=28 | | 19.95+.99m+65.32=144.67 | | 10x+5=2x+45 | | 20q^2-9qr-18r^2= | | 10-4p+35=2-p | | 15p+17q+p-7q-4p= | | -0.04x-x-0.2x=6.2 | | 8-16w=-8(1+2w) | | 8x+2=x-3 | | 4x-9+3x-5+x=7x+2 | | 0.6666667x+6=0.5x+0.25x | | g(h)=-x^2+x-6 | | x^2+y^2-4x-6y+8=0 |

Equations solver categories